CREATING THE SYSTEM OF PROTECTION OF INTELLECTUAL PROPERTY AT UNIVERSITIES - Zajac, Jozef; Modrak, Vladimir; Pitel, Jan; Kokula, Pavel (European Scientific Journal, ESJ, 2014)
The article presents possibilities of intellectual property protection by internal institutionalization of universities. Most Central European universities do not have any systemic institutes of intellectual property protection and this issue is dealt with by various branches of the institution non-systemically. The article illustrates the internal structure of university centers to ensure effective action to ensure the protection of copyright and industrial property rights and licensing of knowledge. Furthermore, interactions within the conceived system and input-output information are elaborated.